1990
DOI: 10.1093/nar/18.9.2817
|View full text |Cite
|
Sign up to set email alerts
|

Complete cDNA sequence encoding the B subunit of human factor XIII

Abstract: Here we report on the complete cDNA sequence of the b-subunit of human factor xI (FXIII). FXII is a blood coagulation protein that is distributed both extracellulary and intracellulary (1). Its enzymatic form acts as a transglutaminase and is also called activated fibrin-stabilizing factor or fibrinoligase (EC 2.3.2.13, protein-glutamine:amine gamma-glutamyltransferase). In blood plasma FXII was described to consist of two catalytic a-subunits and in addition two b-subunits (together MW 320 000).A full length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…RT-QPCR showed that mRNA expression of a-2,3-sialyltransferase 1 (ST3Gal1), which transfers sialic acid with an a-2,3 linkage to Oglycans (27), was similar in the two cell populations (Fig. 4A), but mRNA expression of ST6Gal1, which catalyzes the formation of a-2,6-sialylated N-glycans (28,29), was much greater in plasma cells than in B cells (Fig. 4A).…”
Section: Gal-1 and Gal-8 But Not Gal-3 Promote Plasma Cell Formationmentioning
confidence: 99%
“…RT-QPCR showed that mRNA expression of a-2,3-sialyltransferase 1 (ST3Gal1), which transfers sialic acid with an a-2,3 linkage to Oglycans (27), was similar in the two cell populations (Fig. 4A), but mRNA expression of ST6Gal1, which catalyzes the formation of a-2,6-sialylated N-glycans (28,29), was much greater in plasma cells than in B cells (Fig. 4A).…”
Section: Gal-1 and Gal-8 But Not Gal-3 Promote Plasma Cell Formationmentioning
confidence: 99%
“…The mAb against ST6Gal I was raised against a defined peptide sequence specific for ST6Gal I consisting of 16 amino acids (aa 121-137, NH2-KYKVSYKGPGPGIKFS-COOH) of the human ST6Gal I (Grundmann et al, 1990). The peptide was coupled to KLH via an extra C-terminal cysteine.…”
Section: Reagentsmentioning
confidence: 99%
“…YACs of the CEPH mega YAC library (Chumakov et al, 1992) were selected based on the published presence of sequence tagged sites (STSs) on these YACs. The ICI library and CEPH mega YAC library were screened with cDNA probes of the F13B gene (FXIIIb partial cDNA; Grundmann et al, 1990) and the HF1 gene (pFH1.4a; Estaller et al, 1991). Membranes of the ICI library, screening of the CEPH library, and YAC clones were provided by the YAC Screening Centre Leiden (YSCL), The Netherlands.…”
Section: Yac Library Screeningmentioning
confidence: 99%